Which Hugo? This One! Hugo de Hervorst - Berger, Harald (Vivarium, 2019)
One of the riddles of the history of late medieval philosophy is the identity of a certain Hugo who is frequently quoted in manuscripts as well as in early prints. This article offers solutions to the relevant problems, identifying the work to which these quotations refer. One of the manuscripts presents the author's name as "Hugo de Reyss," Reyss being identified with Rees in North-Rhine/Westphalia. A passage in that work links the author to the University of Paris. Among the Hugos documented at the University of Paris at the relevant time, Hugo de Hervorst is the most promising candidate. Hugo of Hervorst and his family had close relations to Rees. In sum, a chain of arguments leads to the identification of Hugo de Reyss as Hugo de Hervorst, whose academic and ecclesiastical careers can thus be outlined. Documented for the first time in 1372, he died in 1399.